The Treaty of Ghulja reconsidered: Imperial Russian diplomacy toward Qing China in 1851. Issue 2 (July 2019) - Shioya, Akifumi
This work endeavors to analyze the negotiation process of the Treaty of Ghulja between the Russian Empire and Qing China in the summer of 1851. The treaty's format and negotiation method largely followed the examples established by the original Kiakhta Treaty and its subsequent revisions. The Imperial Russian government nevertheless tried to extend the rights articulated in the Kiakhta Treaty to the new commercial treaty in Ghulja, embedding within it new rights equal to those acquired by European powers in Qing China's territories to open free trade in Xinjiang.